Empyema necessitans in an infant due to pseudomonas aeruginosa at a referral hospital in mogadishu, somalia: A case report - Mohamed, Yahye Garad (Radiol Case Rep, 2021)
Empyema necessitans (EN) is a rare complication of bacterial pneumonia, especially in children. It can be caused by many infectious agents, but Mycobacterium tuberculosis is the most common cause of EN. We report a 3-month-old girl who had EN on the 90th day of life, multidrug-resistant P. aeruginosa was isolated from her pleural fluid culture. We could not find another published report about EN caused by Pseudomonas aeruginosa (P. aeruginosa) in an infant. The case highlights that children presenting with fever and chest wall mass should be immediately imaged by chest computed tomography as there might be an urgent need for intervention.